Pemasaran Tempat Wisata Janda Desa Danda Jaya Kecamatan Rantau Bedauh Barito Kuala - Syafril Djaelani; Madayan Madayan; Salahudin Bahri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Activity Community Services is a Management Training and Marketing Places in Danda village Rantau Jaya subdistrict Bedauh expected increase knowledge of SMEs, managers and officials BUMDes village in managing and marketing agro-tourism mushrooms produced by farmers. The method used in community service activities are a combination of prensentasi, Dialok interkatif and debriefing between presenters with the trainees. One marketing technique that can be used is the marketing mix is ​​a blend of a number of marketing tools that companies use to convince the object of marketing or the intended target market. SMEs and BUMDes can increase sales by paying attention to the product, price, place and promotion. In the market products the marketing mix elements coupled with the People, Process and Customer Service. The combination of marketing mix will be able to increase the volume of sales of products and services for SMEs in the District of Barito Kuala Bedauh Rantau South Kalimantan